Transition from special school to post school in youth with intellectual disability: Parents' experiences - Ellman, Emalda Rochelle (Department of Health and Rehabilitation Sciences, 2015)
Transitions from one life stage to the next are considered to be a normal part of every person's life. Transitions have been described as important landmarks in the educational career of youth, as successful transitions prepare them for adult life. When youth with disabilities leave school, the transition to post school does not occur naturally. Research has found that youth with intellectual disabilities and their families find the transition from school to post school to be challenging. In South Africa, Education White Paper 6 on special needs represents the country's plan for addressing shortcomings in the education system. There is still very little information available on the preparation of intellectually disabled youth for their post school future in the South African context. Consequently, parents of intellectually disabled youth face tremendous challenges when their child reaches this transition age. This study aimed to describe parents' experience of the transition of their intellectually disabled youth from special school to post school in the West Coast. A qualitative descriptive study using in-depth interviews was conducted with five parents of youth with intellectual disability. Inductive analysis of the transcripts yielded two themes and six categories. Theme one, "It really hit us hard" had three categories: "feeling uncertain and confused", "managing without peer support" and "mixed feelings". Theme two, "Parental adjustment to post transition life" had three categories: "setting up a routine", "negotiating everyday occupations" and "accessing resources and a support system". The research found that the meanings parents attribute to their experience of transition are significantly influenced by their personal responses and coping strategies in the context they find themselves in during the transition period.